Long-Term Neurocognitive Outcomes of Spring-Assisted Surgery versus Cranial Vault Remodeling for Sagittal Synostosis. Issue 3 (23rd February 2021) - Alperovich, Michael; Runyan, Christopher M.; Gabrick, Kyle S.; Wu, Robin T.; Morgan, Chelsea; Park, Sydney E.; Chapman, Leah A.; Couture, Daniel E.; David, Lisa R.; Persing, John A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: A long-term neurocognitive comparison of patients with sagittal synostosis who underwent spring-assisted surgery or cranial vault remodeling has not been performed. Methods: Patients with sagittal synostosis who underwent spring-assisted surgery or cranial vault remodeling were recruited from Wake Forest School of Medicine and Yale School of Medicine, respectively. Cognitive tests administered included an abbreviated intelligence quotient, academic achievement, and visuomotor integration. An analysis of covariance model compared cohorts controlling for demographic variables. Results: Thirty-nine spring-assisted surgery and 36 cranial vault remodeling patients were included in the study. No significant differences between cohorts were found with respect to age at surgery, sex, race, birth weight, family income, or parental education. The cranial vault cohort had significantly older parental age ( p < 0.001), and mean age at testing for the spring cohort was significantly higher ( p = 0.001). After adjusting for covariates, the cranial vault cohort had significantly higher verbal intelligence quotient (116.5 versus 104.3; p = 0.0024), performance intelligence quotient (109.2 versus 101.5; p = 0.041), and full-scale intelligence quotient (114.3 versus 103.2; p = 0.0032). When included patients were limited to intelligence quotients from 80 to 120, the cranial vault cohort maintained higher verbal (108.0 versus 100.4; p = 0.036), performance (104.5 versus 97.7; p = 0.016), and full-scale (107.6 versus 101.5; p = 0.038) intelligence quotients. The cranial vault cohort had higher visuomotor integration scores than the surgery group (111.1 versus 98.1; p < 0.001). There were no significant differences in academic achievement. Conclusions: Sagittal synostosis patients who underwent cranial vault remodeling had higher intelligence quotient and visuomotor integration scores. There were no differences in academic achievement. Both cohorts had intelligence quotient scores at or above the normal range. Further studies are warranted to identify factors that may contribute to cognitive outcome differences. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.